2002
DOI: 10.1001/archneur.59.9.1453
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Directly Stimulated Muscle Strength in Hemiplegia Due to Stroke

Abstract: Modes of exercise therapy focused primarily on direct strengthening of striated musculature, as in resistive exercise training, are strategically questionable. Whether other approaches may be more effective remains to be proved. The central disability of the upper motor neuron syndrome is failure of rapid coordinated adjustment of graded high-frequency motoneuron firing in purposeful complex synergies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 39 publications
3
23
3
Order By: Relevance
“…In addition, potentiation may also occur when multiple synergistic muscles are activated during functional movements (De Luca and Erim 2002;Huang and Abraham 2001). Additionally, Landau and Sahrmann (2002) demonstrated that the paretic tibialis anterior muscle of individuals with stroke had lower levels of maximal voluntary torque, but not electrically stimulated force, compared with control subjects, suggesting that the central regulation of muscle activation may be disrupted. Such observations agree with Tang and Rymer (1981) who found that the amount of EMG produced per unit force was greater in the paretic elbow flexor muscles compared with controls and they attributed this increased recruitment from a compensation to the reduced mean motor unit discharge rate that they observed in the paretic muscles.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…In addition, potentiation may also occur when multiple synergistic muscles are activated during functional movements (De Luca and Erim 2002;Huang and Abraham 2001). Additionally, Landau and Sahrmann (2002) demonstrated that the paretic tibialis anterior muscle of individuals with stroke had lower levels of maximal voluntary torque, but not electrically stimulated force, compared with control subjects, suggesting that the central regulation of muscle activation may be disrupted. Such observations agree with Tang and Rymer (1981) who found that the amount of EMG produced per unit force was greater in the paretic elbow flexor muscles compared with controls and they attributed this increased recruitment from a compensation to the reduced mean motor unit discharge rate that they observed in the paretic muscles.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…3 This loss of force production occurs because of an interruption of the pyramidal tract. 4 In the early phase of recovery, many patients are unable to maintain an upright position in sitting or standing, and have no ability to move the affected arm.…”
Section: Central Weakness: Loss Of Force Productionmentioning
confidence: 99%
“…[20][21][22] Today, the nature of spasticity, its underlying mechanisms, and its relevance to rehabilitation practice are being widely investigated and debated. 3,23,24 At the same time, the increasing popularity of medical interventions for spasticity (for example, botulotoxin injections) suggests its treatment remains a priority within the medical community.…”
Section: Spasticity and Hypertonicitymentioning
confidence: 99%
“…Ada et al 2 discovered that stroke subjects were relatively stronger when both flexors and extensors were in their lengthened range and relatively weaker when the muscles were in their shortened ranges. However, the contractile capacity of the paretic muscle itself is not altered after stroke 5 ; rather, there may be a deficient central recruitment of motor units. Some investigators have suggested that after stroke, impairment of voluntary strength is associated with deficient motor unit recruitment and firing frequencies insufficient to generate a fused tetanus of the involved motor units.…”
mentioning
confidence: 99%